Nilai Moderasi Beragama Dalam Wasiat Wajibah Kepada Non- Muslim Melalui Penerapan Maqasid Syari’ah - Agustiar (Universitas Negeri Jakarta, 2025)
This research examined decision number 263/P.Dt.G/2007/Pta.Sby to identify the values of religious moderation implemented by the judge. This research aims to find out and analyze the values of religious moderation in the granting of mandatory wills to non-Muslims through the application of maqasid al-syari'ah in decision number 263/P.Dt.G/2007/Pta.Sby. The source of information regarding this matter is decision number 263/p.dt.g/2007/pta.sby. The decision was analyzed using content analysis. The steps taken are collecting data, organizing it, presenting it in writing, and drawing conclusions. The research findings show that the value of religious moderation implemented by religious court judges in the decision above, have a positive impact includes: maintaining peace and stability in the family environment, promoting peace and prosperity in society, ensuring the protection of property, providing protection for religious interests, protecting the existence of family harmony, and ensuring social justice in the community, and reflecting the flexibility of Islamic teachings.